An optimized method for IgE-mediated degranulation of human lung mast cells - Gong, Yitao; Johnsson, Anna-Karin; Säfholm, Jesper; Al-Ameri, Mamdoh; Sachs, Erik; Vali, Kasra; Nilsson, Gunnar; Rönnberg, Elin (Frontiers in Immunology, 2024)
Background: Mast cells are critically involved in IgE-mediated diseases, e.g., allergies and asthma. Human mast cells are heterogeneous and mast cells from different anatomical sites have been shown to respond differently to certain stimuli and drugs. The origin of the mast cells is therefore of importance when setting up a model system, and human lung mast cells are highly relevant cells to study in the context of asthma. We therefore set out to optimize a protocol of IgE-mediated activation of human lung mast cells. Methods: Human lung mast cells were extracted from lung tissue, obtained from patients undergoing pulmonary resection, by enzyme digestion and mechanical disruption followed by CD117 MACS enrichment. Different culturing media and conditions for the IgE-mediated degranulation were tested to obtain an optimized method. Results: IgE-crosslinking of human lung mast cells cultured in serum-free media gave a stronger response compared to cells cultured with 10 percent serum. The addition of SCF did not enhance the degranulation. However, when the cells were put in fresh serum-free media 30 minutes prior to the addition of anti-IgE antibodies, the cells responded more vigorously.Maximum degranulation was reached 10 minutes after addition of anti-IgE. Both CD63 and CD164 were identified as stable markers for the detection of degranulated mast cells over time, while the staining with anti-CD107a and Avidin started to decline 10 minutes after activation. The levels of CD203c and CD13 did not change in activated cells, and therefore cannot be used as degranulation markers of human lung mast cells. Conclusions: For an optimal degranulation response, human lung mast cells should be cultured and activated in serum-free media. With this method, a very strong and consistent degranulation response with low donor to donor variation is obtained. Therefore, this model is useful for further investigations of IgE-mediated mast cell activation and exploring drugs that target human lung mast cells, for instance in the context of asthma.